Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

I agree with mirhaque on answer choice (E). How did you get 3 for r, thearch? The equation can be expanded to:

x^2+ax+b = x^2+2rx+r^2

I canceled out x^2 on both sides, leaving:

ax+b = 2rx+r^2

Statement (I) says b=9, but that still leaves you with 3 unknowns.
Statement (II) says a=-6, and that still leaves you with 3 unknowns.
Combinining (I) and (II) still leaves 2 unknowns.

my reasoning was:
distinguish between two sides of the equation
so you resolve the first
x^2-6x+9=0 --> only one root because 36-4*9=0
so the solution of it is (6+-0)/2=3 (X found)
then you have
(x+r)^2=0 -> r=-3

but I'm now considering that the stem doesn't tell us that x^2-6x+9=(x+r)^2=0 and without that you remain with two unknowns so it should be (E)

Soln: Lets first open up the given equation, => x^2+ax+b=(x+r)^2 => x^2+ax+b=x^2+2rx+r^2

now since coefficients of x^2 are equal, so matching the other coefficients on both sides, ax = 2rx => a = 2r => eq(1) b = r^2 => eq(2)

Considering statement 1 alone, since b = 9 and we have b = r^2 therefore r = +3 or -3 Since we have two values of r, Statement 1 alone is insufficient

Considering statement 2 alone, since a = -6 and we have a = 2r therefore r = -3 Since we have just one unique value of r, Statement 2 alone is sufficient